USAGE OF OLIGOPEPTIDES IN THE TREATMENT OF VIRAL INFECTIONS IN CHILDREN - PRELIMINARY RESULTS - A. G. Bokovoy; L. F. Makkaveeva; N. B. Tanina; Yu. V. Polyakova; O. A. Volodina (LLC "Diagnostics and Vaccines", 2015)
We compared clinical and laboratory data in 2 groups of children (The first group 62 ARVI patients with bacterial complications of herpes virus infection who were treated by transfer factors as a part of the complex therapy. The second group was comprised of 72 children with the same pathology who did not receive this biological additive). The patients receiving transfer factors displayed smooth course of ARVI with pneumonia, and a tendency to accelerated normalization of cellular immunity at herpes virus infection. The follow-up of 112 sickly children shows that the incidence of recurrent ARVI in 67 patients receiving transfer factor was reliably reduced by 2 times, compared to that of 45 children who did not receive this product.